2012
DOI: 10.1111/irv.12063
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective serological survey of influenza viruses in backyard pigs from Mexico City

Abstract: BackgroundIn the present study, we analyzed the presence of antibodies to four different influenza viruses (pH1N1, hH1N1, swH1N1, and swH3N2) in the sera of 2094 backyard pigs from Mexico City. The sera were obtained between 2000 and 2009.ObjectivesThe aim of this study was to perform a retrospective analysis of the 2000–2009 period to determine the seroprevalence of antibodies against pH1N1, hH1N1, swH1N1, and swH3N2 viruses in sera obtained from backyard pigs in Mexico City.MethodsAntibody detection was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
(34 reference statements)
0
13
0
1
Order By: Relevance
“…Interestingly, exposure to the pH1N1 virus was found in the majority of positive animals, regardless of the type of PPU. Introduction of pandemic viruses into pigs has been documented in other countries in Central America and the Caribbean 27, 28, 36. In Guatemala, reverse zoonotic transmission from humans is the most likely explanation to the origin of the pH1N1 viruses circulating in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, exposure to the pH1N1 virus was found in the majority of positive animals, regardless of the type of PPU. Introduction of pandemic viruses into pigs has been documented in other countries in Central America and the Caribbean 27, 28, 36. In Guatemala, reverse zoonotic transmission from humans is the most likely explanation to the origin of the pH1N1 viruses circulating in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…When two subtypes were present in a same sample, the one with highest titres showed higher specificity (Gaitán‐Peredo, ; Saavedra‐Montañez et al., ). Table shows the titres of specific antibodies against H1N1 swIAV detected in all farms determined as only positive for H1N2, to assess the specificity of positive results.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study identified antibodies against swine-like H1N1, A(H1N1)pdm09, H3N2, and human-like H1N1 viruses in backyard swine in Mexico between 2000 to 2009. This investigation retrospectively determined that the classical-swine H1N1 virus was most widely present in Mexican swine before the 2009 influenza pandemic [305]. Further, a significant number of swine experiencing respiratory illness had H1N1 or H3N2 virus antibodies in commercial piggeries in Sonora Province of Mexico during October 2008-March 2009.…”
Section: Mexicomentioning
confidence: 99%